Claims to Legitimacy Matter: Why Sanctions Fail to Instigate Democratization in Authoritarian Regimes - Julia Grauvogel; Christian von Soest (German Institute of Global and Area Studies (GIGA), 2013)
International sanctions have been one of the most commonly used tools of Western foreign policy in the post-Cold War era to instigate democratization globally. However, despite long-term external pressure through sanctions imposed by the European Union, the United States and/or the United Nations, nondemocratic rule in cases such as Belarus, Cuba, Eritrea, Iran, North Korea and Syria has proven to be extremely persistent. In this paper, we analyze a new global dataset on sanctions from 1990 to 2011 and assess which international and domestic factors account for the persistence of nondemocratic rule in targeted regimes. The results of a fuzzy set Qualitative Comparative Analysis (fsQCA) of 120 episodes of sanctions provide new insights for the research on both sanctions and authoritarian regimes. Most significantly, sanctions strengthen nondemocratic rule if the regime manages to incorporate their existence into its legitimation strategy. Such a rally-round-the-flag effect occurs most often in cases where comprehensive sanctions targeting the entire population are imposed on regimes that enjoy strong claims to legitimacy and have only limited linkages to the sanction sender.
Keywords: 300; sanctions; claims to legitimacy; authoritarian regimes; democratization